Neonatal seizures: clinical manifestations and etiology - Daisy Widiastuti; Irawan Mangunatmadja; Taralan Tambunan; Rulina Suradi (Paediatrica Indonesiana, 2006)
Background Neonatal seizures or fits are signs of central ner-vous system (CNS) diseases, metabolic disorders, or other dis-eases disrupting the CNS. Neonatal seizures are poorly classi-fied, under-recognized and often difficult to treat. It is important torecognize the type of neonatal seizures that might be the only signof a CNS disorder.Objective To recognize the type and etiology of neonatal sei-zures in several hospitals in Jakarta.Methods This was an observational case series study on full-termand preterm infants who had seizures during hospitalization in CiptoMangunkusumo, Harapan Kita, and Fatmawati Hospitals betweenJanuary-June 2005. Neonatal seizures were defined as seizuresoccurring in the first 28 days of life of a term infant or 44 completedweeks of the infant’s conception age of preterm infant.Results There were 40 neonates who born within the study periodand had seizures. Girls were outnumbered boys. Most neonateswere full-term with birth weight of more than 2500 grams. Analy-ses were done on 38 neonates with epileptic and non-epilepticseizures, while the other two who had mixed clinical manifestationwere not included. Most seizures occurred in the first 3 days of life(23/38). The most common type was focal clonic (12/14) followedby general tonic (11/24) and motor automatism or subtle (10/24).The most common etiology was hypoxic ischemic encephalopa-thy (HIE) (19/38) followed by metabolic disturbances, mainly hy-pocalcaemia (11/38).Conclusion Common types of seizures in neonates were focalclonic, general tonic, and motor automatism (subtle). The mostcommon etiology was HIE followed by metabolic disturbances,mainly hypocalcaemia